The Correlations among Critical Thinking, Linguistic Intelligence, and Writing Ability of the Sixth Semester Students of FKIP PGRI University of Palembang - Umi Dian Adhitya WN; Indawan Syahri; Baginda Simaibang (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThis article is concerned with the inquiry on the correlations among critical thinking, linguistic intelligence and writing ability. This study is aimed to investigate the empirical evidence about critical thinking and linguistic intelligence and its correlation to writing ability. The population of this study encompassed all the sixth semester students of Department of English Education of FKIP PGRI University of Palembang of which total is 108 students. From the population, only 36 students were taken as the samples. The systematic non-random sampling technique was used in recruiting the samples. Data were collected through tests and questionnaire. Data were analyzed by using Pearson Product Moment and multiple regression to find out the correlations among critical thinking and linguistic intelligence simultaneously on writing ability. Findings showed that there was significant correlation between critical thinking ability and writing ability, and between linguistic intelligence and writing ability. Multiple regression indicates that there were significant influences of critical thinking and linguistic intelligence simultaneously on writing ability. In conclusion, there is significant correlation among critical thinking, linguistic intelligence, and writing ability. At the same time, both critical thinking and linguistic intelligence affect writing ability of the sixth semester students of FKIP PGRI University of Palembang. Keywords: critical thinking, linguistic intelligence, writing ability, correlation, multiple  regression.